Educação moral e cívica: entre comemorações e acusações, um projeto de pátria para o Brasil (ES, 1969-1975) - Abreu, Louise Storni Vasconcelos de (2016)
This research is to observe how was the representation of a homeland project, formulated by the government during the military dictatorship in Brazil, through the Moral and Civic Education discipline. This, the general objective is to analyze the cultural objects (historical sources) that helped the Brazilian government to create a representation of the country, which should be appropriate for the Brazilians. In addition, we use the specific objectives to understand the moral notions of representation and civility throughout the twentieth century; understand how cultural objects (historical sources) helped the government to create a representation of the country, which should be appropriate for the Brazilians; see how civic practices of commemoration of the 150th anniversary of Brazil's independence form "given to read" in the state of the Espírito Santo through the major newspaper; interpret as a cultural practice of civic celebration contributed to the formulation of a Homeland project for Brazil; analyze the control as a cultural practice of deterrence, which also contributed to the government's Fatherland project. Our hypothesis is that the sources, understood as cultural objects, immersed in a particular school culture, were participants of a homeland project, in addition to a national project. Therefore, we raise the following issue: How the Moral and Civic Education contributed to the formulation of a country project to Brazil by the government during the military dictatorship, specifically in the state of Espírito Santo? By proposing an approach that enables more detailed understanding of a fundamental moment in the history of Brazilian education, we use as documentary corpus Decree Law 869 of 12 September 1969 introducing discipline in the country, and the Methodological Guide for MEC books - history, the Curriculum Guidelines of the State Secretariat of the Espírito Santo and the Little Encyclopedia of moral and civics to understand how the values and concepts of morality and civility were given to read in relation to the representations of the country project proposed by the Dictatorship Military. To assist with this understanding, we also use publications of the newspaper The State of Espírito Santo Gazette to understand how civic moments on the Sesquicentennial of the Independence of Brazil were used as part of the appropriation of the sense of home by Brazilian citizens, especially young people and children school age of the Holy Spirit. In addition, we use the documents Dops the APEES Fund on teachers accused of communist tendencies, teachers that they put in doubt the moral and civic education, both as a discipline as educational practice, which should be monitored and restrained in order to sustain representations of existing cultural practices.